Cover Feature: Aza‐oxyallyl Cations and Their Applications in (3+m) Cycloaddition Reactions (Eur. J. Org. Chem. 47/2022). Issue 47 (8th December 2022) - Deeksha,; Singh, Ritesh
Abstract : The Cover Feature illustrates the generation of diverse N‐heterocyclic scaffolds and N‐architectures generated via 3+m cycloaddition reactions or alkylation of a common aza‐oxyallyl cation intermediate in analogy to a flower where various petals originate from the same centre. Cover picture created by Ms. Deeksha and Dr. Ritesh Singh. More information can be found in the Review by Deeksha and R. Singh .